2021
DOI: 10.1186/s12199-021-00975-9
|View full text |Cite
|
Sign up to set email alerts
|

Food safety knowledge, attitude, and hygiene practices of street-cooked food handlers in North Dayi District, Ghana

Abstract: Background Food safety and hygiene are currently a global health apprehension especially in unindustrialized countries as a result of increasing food-borne diseases (FBDs) and accompanying deaths. This study aimed at assessing knowledge, attitude, and hygiene practices (KAP) of food safety among street-cooked food handlers (SCFHs) in North Dayi District, Ghana. Methods This was a descriptive cross-sectional study conducted on 407 SCFHs in North Day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
88
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 45 publications
16
88
7
1
Order By: Relevance
“…In the current study, having formal education had increased hygienic food handling practices of food handlers, which is consistent with the study conducted by Dagne et al 38 and Tuglo et al 40 This maybe expressed as the higher the education level of food handlers, the more likely to perform good hygienic food handling practices. But, other study in Ghana found that food handlers with a low level educational status were more likely to have hygienic food handling practices than those with a higher educational status, contrary to our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, having formal education had increased hygienic food handling practices of food handlers, which is consistent with the study conducted by Dagne et al 38 and Tuglo et al 40 This maybe expressed as the higher the education level of food handlers, the more likely to perform good hygienic food handling practices. But, other study in Ghana found that food handlers with a low level educational status were more likely to have hygienic food handling practices than those with a higher educational status, contrary to our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Food handlers who received food safety training were 5.38 times more likely to gain experience with hygienic food handling practices than those who did not. The findings of research conducted in Ethiopia 38 , 39 and Ghana 40 support this conclusion. This could be because food handlers who did receive food safety training may have the necessary knowledge and experience because they may have received professional advice during training 41 in terms of food hygiene as well as transmission and prevention of foodborne diseases.…”
Section: Discussionmentioning
confidence: 53%
“…The multivariable logistic regression results showed that being a model household head (having received safety training) was a strong predictor of good food safety practices, which showed that the odds of performing good food safety practices among model household heads was 2.99 times higher compared to their counterparts. The result is corroborated by previous, similar studies, conducted in Debarq Town, 29 Gondar City, 7 Abobo district, 16 and Hawassa City, South Ethiopia, 25 Ghana, 33 Bangladesh, 34 Imo State, Nigeria, 27 and Saudi Arabia. 35 This could be explained by household heads who have received food safety training having a better understanding of safe food handling practices compared to household heads without food safety training.…”
Section: Discussionsupporting
confidence: 89%
“…The factor that was associated with food safety KAP was the education level which was statistically significantly associated with poor food safety practice among OFSP processors. This results compares well with the study by (Tuglo et al, 2021) in North Dayi District, Ghana, who found that among street-cooked food handlers in Ghana, the food handlers with secondary education were 4 times good at hygiene practices of food safety likened to no education [aOR=4.06, p=0.003]. Another study in Kenya by (Malavi, 2017) also found the overall mean percentage scores of 81% for knowledge, attitude, practices and overall KAP.…”
Section: Discussionsupporting
confidence: 83%